2015
DOI: 10.4314/star.v4i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging, Antimicrobial and Insecticidal Efficacy of <i>Parmotrema cristiferum</i> and <i>Dirinaria applanata</i>

Abstract: AbstrLichens are self-supporting symbiotic association of mycobiont and photobiont. The present study was conducted to investigate antimicrobial, insecticidal and radical scavenging potential of methanol extract of two macrolichens and Dirinaria applanata (Fée) D.D. Awasthi. Antibacterial activity was tested against a panel of 5 bacteria by Agar well diffusion assay. Minimum inhibitory concentration was determined against 2 bacteria by broth dilution method. Antifungal efficacy was determined against 5 molds b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Dirinaria genus contains 29 species distributed across the world. The pharmacological screening of this genus found to have radical scavenging, antimicrobial and insecticidal effects 8 . On the other hand, Ramalina genus has about 246 species distributed around the world, of which only 118 species were investigated for their chemical and biological studies.…”
Section: Vinay Bharadwaj Tatipamula Et Almentioning
confidence: 99%
“…Dirinaria genus contains 29 species distributed across the world. The pharmacological screening of this genus found to have radical scavenging, antimicrobial and insecticidal effects 8 . On the other hand, Ramalina genus has about 246 species distributed around the world, of which only 118 species were investigated for their chemical and biological studies.…”
Section: Vinay Bharadwaj Tatipamula Et Almentioning
confidence: 99%
“…and Aspergillus flaus isolated from seeds of sorghum. Kekuda et al (2015) showed the potential of P. cristiferum to inhibit mycelial growth of fungi viz. Alternaria sp., Helminthosporium sp., Fusarium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Awasthi is a foliose lichen belongs to the Dirinaria genus which possesses anticaries, antioxidant, antimicrobial, cytotoxic and larvicidal activities. [12][13][14][15] However, there are no pharmacological study reports revealing antiinflammatory potentiality of D. consimilis and also keeping in mind of the aforementioned the biological profile of Dirinaria genus and the drawbacks of anti-inflammatory therapeutics, we anticipated Dirinaria consimilis might be active good source for anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 97%